PENGARUH PROGRAM BINA DIRI TERHADAP KEMANDIRIAN ANAK TUNAGRAHITA - Kurniawan, Emil (Psympathic : Jurnal Ilmiah Psikologi, 2018)
This research aims to know the effectiveness of self-improvement application toward autonomy of mentally disabled children (medium category) at school of special needs students (SLB) Abc Argasari Yayasan Lestari Tasikmalaya. Â Quasi-experiment using single subject research design and multiple baseline design is used. Collecting data used observation with Rating Scale instrument and interview. Result shows that there is an increasing score in treatment phases. It ca be concluded that self-improvement program effect the autonomy of mentally disabled children at Â School of special needs students (SLB) Abc Argasari Yayasan Lestari Tasikmalaya.